Improving Grassroots Service Delivery Using Results-Based Financing in Vietnam : An Assessment of the Nghe An Pilot - Nguyen, Ha Thi Hong (World Bank, Washington, DC, 2018)
Over the last decade, results-based financing (RBF) health programs have been implemented in several countries at different levels of income. Due to its requirement of rigorous verification of results as a condition for financing, as well as a number of accompanying measures to help achieve the results, RBF has a promise of value for money. RBF's potential for improving the performance of the service delivery system has led the government of Vietnam to undertake a pilot of RBF in the Nghe An province as part of a World Bank funded operation. The main objective of the pilot was to experiment an RBF approach in the Vietnam context, where public sector providers have been receiving budget allocation based on inputs rather than performance. A secondary objective was to test the effects of RBF in improving quality of care at the grassroots level and in addressing the challenges of emerging noncommunicable diseases. The intervention included quality improvement at the district level and both quality and quantity of services at commune health station.